Ludotherapy and Clown therapy in dental care for patient with prader-willi syndrome: Case report - Duarte Bonavides, Paulo Ricardo (2018)
The Prader-Willi Syndrome (PWS) is a complex genetic alteration affecting appetite, growth, metabolism, cognitive func-tion and behavior. It is characterized by low muscle tone, low height, incomplete sexual development, behavioral difficul-ties, and especially by chronic feelings of insatiable hunger and slow metabolism threatening life due to obesity. Changes in behaviour are very common and are related to the difficulty of dental treatment approach. We report the case of a 11-year-old patient, female, diagnosed with PWS, with high risk obesity and serious behavioural alterations. Clinically, she present-ed active caries lesions, periodontitis and dental extraction need. Conditioning for dental treatment was performed using techniques of ludotherapy and play therapy during 6 sessions, allowing the proposed interventions. It could be concluded that the use of both conditioning interventions decreased the anxiety facilitating the professional-patient bond, appearing as effective techniques for the outpatient care on pediatric patients dental control with severe behavioural alterations.